Maternity and breakdown: therapeutic consultations during pregnancy and postpartum - Granato, Tania Mara Marques; Aiello-Vaisberg, Tania Maria José (Paidéia (Ribeirão Preto), 2009)
Five clinical vignettes were developed based on therapeutic consultations with pregnant women and mothers in order to psychoanalytically investigate the hypothesis that primitive psychic states are originated by motherhood. The winnicottian perspective, according to which therapists adopt the holding as the basis of every therapeutic intervention, was particularly productive in terms of relieving maternal suffering as well as to enable a personal appropriation of motherhood. Some recommendations are forwarded to psychologists with a view to redirect their focus to maternal needs so as to favor the establishment of a healthy mother-infant relationship, through the promotion of maternal well-being.